Extendingof the Life of Active Parts of Cold-Moulding Tools - Jan Moravec (Communications - Scientific letters of the University of Zilina, 2015)
Heat treatment of active components of cold–moulding tools is a necessary operation to guarantee their functionality. The tools made by this method lost required quality of durability and period of service and losses caused by their frequent exchange are high. One way we can stop it is by coating the active parts of pressing tools by thin, hard and abrasion resistant deposit that is suitable by definite method of the tool stress.